Selected aspects of the operation of dual active bridge DC/DC converters - Bachman, Serafin; Turzyński, Marek; Jasiński, Marek (Bulletin of the Polish Academy of Sciences Technical Sciences, 2024)
This review paper discusses the concept of a bidirectional dual active bridge (DAB) DC/DC converter. Practical applications and control methods are explored, and various types of DAB converters are introduced and characterized. Aspects of operation are discussed, and enriched by the results of theoretical analyses, simulations, and experimental measurements of the original authors’ work.